2019
DOI: 10.1002/hep.30200
|View full text |Cite|
|
Sign up to set email alerts
|

DDX24 Mutations Associated With Malformations of Major Vessels to the Viscera

Abstract: Our results provide the first link between DDX24 and vascular malformation, and indicate a crucial role for DDX24 in endothelial cell functions. These findings create an opportunity for genetic diagnosis and therapeutic targeting of malformations of vessels to the viscera. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(69 reference statements)
0
12
0
Order By: Relevance
“… 29 Our previous research revealed that DDX24 mutations were pathogenic factors of vascular deformities and played a significant role in the migration ability of endothelial cells. 10 Based on published reports, DDX24 functions as a modulator of the p300-p53 axis by suppressing the p300-mediated acetylation of p53, which promotes the proliferation of osteosarcoma cells and lung carcinoma cells. 11 Additionally, other studies revealed that a perturbation of DDX24 inhibited colon cancer and gastric cancer growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Our previous research revealed that DDX24 mutations were pathogenic factors of vascular deformities and played a significant role in the migration ability of endothelial cells. 10 Based on published reports, DDX24 functions as a modulator of the p300-p53 axis by suppressing the p300-mediated acetylation of p53, which promotes the proliferation of osteosarcoma cells and lung carcinoma cells. 11 Additionally, other studies revealed that a perturbation of DDX24 inhibited colon cancer and gastric cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“… 8 DDX24 is an important member of the DEAD-box RNA helicases carrying a conserved Asp-Glu-Ala-Asp (D-E-A-D) motif. 9 Based on our recent findings, a mutated DDX24 gene could cause vascular malformations, 10 and previous studies have revealed that DDX24 is upregulated in multiple human cancer cells, inhibiting cell growth by inducing cell cycle arrest and senescence in osteosarcoma cells. 11 Moreover, DDX24 also regulates the proliferation of colon cancer and gastric cancer cells.…”
Section: Introductionmentioning
confidence: 94%
“…Using cell culture models and zebrafish knockouts they determined that single nucleotide polymorphism mutations in DDX24, a gene coding for a DEAD box helicase, are responsible not only for the MOVLD syndrome but could also be found in some sporadic cases of vascular malformation, and that DDX24 is involved in early vascular development. 18 In this patent document the inventors proceed to identify antagonists of the cysteinyl leukotriene receptor-1 as agents to treat or prevent such malformations. These are the asthma drugs based on the ''lukast'' class of agents (motelukast, zafirlukast, and pranlukast) but also the older necrodomil.…”
Section: A Nonresorbable Antibiotic Prevents Sickle Cell Vaso-occlusive Crisesmentioning
confidence: 99%
“… 10 , 11 In previous studies, DDX24 was associated with cancer development, 12 viral infection, 13 and vascular malformation. 14 However, the role of DDX24 in developing different tumors was complicated, 6 , 15 and the correlation between DDX24 and NSCLC remains unclear and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%